2005
DOI: 10.3171/spi.2005.3.6.0417
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of adjacent-segment disease in patients treated with cervical fusion or arthroplasty: a prospective 2-year study

Abstract: Object. The authors compared the incidence of radiologically documented changes and symptomatic adjacent-level cervical disc disease after single-level discectomy and subsequent cervical fusion or arthroplasty in two independent prospective clinical studies. Methods. The patients were treated with the Affinity Anterior Cervical Cage System or the Bryan Artificial Cervical Disc. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
219
2
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 336 publications
(236 citation statements)
references
References 23 publications
4
219
2
8
Order By: Relevance
“…One was modified hilibrand criteria with radiography [1], and the other was with MRI and CT. We defined ASD as all kinds of degenerative changes (e.g. posterior osteophyte, decrease disc height C25 %, disc signal change, disc herniation, ALL and PLL calcification) at final MRI and CT than preoperative MRI and CT [11]. Various measurements were performed on lateral view of cervical spine radiographs in the neutral and dynamic flexion-extension lateral radiographs obtained at each study point.…”
Section: Subjects and Study Designmentioning
confidence: 99%
See 2 more Smart Citations
“…One was modified hilibrand criteria with radiography [1], and the other was with MRI and CT. We defined ASD as all kinds of degenerative changes (e.g. posterior osteophyte, decrease disc height C25 %, disc signal change, disc herniation, ALL and PLL calcification) at final MRI and CT than preoperative MRI and CT [11]. Various measurements were performed on lateral view of cervical spine radiographs in the neutral and dynamic flexion-extension lateral radiographs obtained at each study point.…”
Section: Subjects and Study Designmentioning
confidence: 99%
“…Yet, previous studies have reported cases of ASD after ACDF [5,6]. ASD rates varied from 25 to 92 % during a long follow-up period [1,[7][8][9][10][11]. However, previous studies on ASD were done only using radiography or CT. MRI is most sensitive in assessing the degenerative change of a disc, and this is the first study to investigate the incidence and prevalence of adjacent segment disease by radiography, CT and MRI at cervical spine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When more than one study addressed the outcome parameters in question, the results were consistent. The available evidence showed directness, meaning Heller [10] Cheng [5] Anderson [1] Mummaneni [13] Nabhan [15] Robertson [17] Country that studies compared the two alternatives in question head to head and addressed the same question as in our research question with respect to population, comparator and outcome. In summary, the strength of evidence for CTDR compared with fusion is moderate.…”
Section: Overall Study Qualitymentioning
confidence: 83%
“…They occurred in maximal one-third of patients in both groups. One study demonstrated a significantly higher rate of ADD in the fusion group [17], however, the rate of secondary surgical procedures was not statistically different between the groups (up to 5% of prothesis-patients and up to 9% of fusionpatients had to undergo a re-operation). No procedurerelated deaths were reported.…”
Section: Safety Of Ctdr Compared With Fusionmentioning
confidence: 97%